The Effect of Practical Learning and Field Work Practical Experience on the Work Readiness of Vocational School Students in The Expertise of Building Design, Modeling and Information - Brayen Juang Mulya Putra; Muhammad Aris Ichwanto; Eko Suwarno; Imam Alfianto; Tee Tze Kiong (Badan Penerbit STIEPARI Press, 2025)
Vocational High Schools (SMKs) are educational institutions that emphasize equipping students with specific skills that can be directly applied in the workforce, aiming to reduce unemployment rates. However, unemployment in Indonesia remains significantly high among SMK graduates, which is largely attributed to the low work readiness of students. This study aims to examine the influence of practical learning and field work practical experience (PKL) on the work readiness of class XII students in the Building Design, Modeling, and Information Expertise Program (DPIB) at SMK Negeri 6 Malang, both partially and simultaneously. The research employed a quantitative approach using a saturated sampling technique, with all 89 students of class XII DPIB participating as respondents. Data collection was conducted through structured questionnaires and observations. The data were analyzed using descriptive statistics, prerequisite tests, multiple regression analysis, multiple correlation analysis, and calculations of relative and effective contributions, assisted by IBM SPSS Statistics software. The results indicate that both practical learning and field work experience have a significant and positive effect on students’ work readiness. When analyzed partially, each variable contributes differently: practical learning accounts for an effective contribution of 15.9% while field work experience contributes 48.2%. In terms of relative contribution, practical learning accounts for 24.8% and field work experience 75.2%. Collectively, these findings demonstrate that practical learning and field work experience significantly enhance the readiness of students to enter the workforce. This highlights the importance of integrating hands-on learning experiences and real-world field work into vocational education to better prepare students for professional environments and improve their employability. The study recommends that SMKs continue to strengthen practical learning curricula and provide ample field work opportunities to ensure graduates possess both the technical skills and work readiness necessary for successful employment.